Write a Scientific Paper (WASP): Past and anticipated trends in cardiology service requirements at Mater Dei Hospital, Malta. (February 2019) - Grech, Victor; Aquilina, Oscar; Cassar, Andrew; Xuereb, Robert
Abstract: Introduction: The requirement for medical services fluctuates. This study was carried out in order to attempt to extrapolate the service requirements for various cardiology services at Mater Dei Hospital, Malta over the coming five years, based on service demands from previous years. Methods: Past annual data was obtained from hospital records for various services (to 2017). Linear regression was carried out using a bespoke Excel™ spreadsheet in order to extrapolate possible services requirements up to 2022. Results: All services are expected to increase, with forecasts ranging between 41 and 354%, depending on services being considered. Discussion: It is easy to "get on with it" and perform the work required at the workplace but this study has shown that it is equally important to anticipate demands lest lack of planning leads to long and important waiting lists for critical diagnostics and treatments. Health care provision requirements are increasing worldwide. Even using conservative estimates and in the absence of the creation of new services, the demands for extant services are likely to continue to grow. Unless medium term plans are made for hardware, software, physical space and staffing, and the funding thereof, waiting lists for investigations in this speciality are bound to rise. This may be mitigated by novel treatments but since these cannot be predicted, it would be safer and wiser to plan ahead lest we are overwhelmed. This paper has also shown how WASP (Write a Scientific Paper) precepts can be applied to elegantly study a problem and write up a paper.